Epidemiological analysis of serum anti‐Pseudomonas aeruginosa PcrV titers in adults. (February 2016) - Yasumoto, Hiroaki; Katoh, Hideya; Kinoshita, Mao; Shimizu, Masaru; Hamaoka, Saeko; Akiyama, Koichi; Naito, Yoshifumi; Sawa, Teiji
ABSTRACT: Of the various virulence mechanisms of the opportunistic pathogen Pseudomonas aeruginosa, the type III secretion system (TTSS) has been characterized as a major factor associated with acute lung injury, bacteremia and mortality. In addition, PcrV, a component protein of the TTSS, has been characterized as a protective antigen against infection with P. aeruginosa . This study comprised an epidemiological analysis of serum anti‐PcrV titers in a cohort of Japanese adults. From April 2012 to March 2013, serum anti‐PcrV titers of 198 volunteer participants undergoing anesthesia for scheduled surgeries were measured. The median, minimum and maximum serum anti‐PcrV titers among the 198 participants were 4.09 nM, 1.01 nM and 113.81 nM, respectively. The maximum peaks in the histogram were within the anti‐PcrV 2.00–4.99 nM titer range; values for 115 participants (58.1%) were within this range. Anti‐PcrV titers were more than approximately three‐fold greater (>12 nM) than the median value in 21 participants (10.6%). Ten‐year interval age increases, history of treatment for traffic trauma, and a history of past surgery each showed statistically significant associations with higher anti‐PcrV titers (i.e., >10 nM) than did the other factors assessed by binomial analysis. This study revealed a considerable variation in anti‐PcrV titers in adult subjects without any obvious histories of infection with P. aeruginosa .